Automated Expansion of Primary Human T Cells in Scalable and Cell‐Friendly Hydrogel Microtubes for Adoptive Immunotherapy. Issue 15 (11th May 2018) - Lin, Haishuang; Li, Qiang; Wang, Ou; Rauch, Jack; Harm, Braden; Viljoen, Hendrik J.; Zhang, Chi; Van Wyk, Erika; Zhang, Chi; Lei, Yuguo
Abstract: Adoptive immunotherapy is a highly effective strategy for treating many human cancers, such as melanoma, cervical cancer, lymphoma, and leukemia. Here, a novel cell culture technology is reported for expanding primary human T cells for adoptive immunotherapy. T cells are suspended and cultured in microscale alginate hydrogel tubes (AlgTubes) that are suspended in the cell culture medium in a culture vessel. The hydrogel tubes protect cells from hydrodynamic stresses and confine the cell mass less than 400 µm (in radial diameter) to ensure efficient mass transport, creating a cell‐friendly microenvironment for growing T cells. This system is simple, scalable, highly efficient, defined, cost‐effective, and compatible with current good manufacturing practices. Under optimized culture conditions, the AlgTubes enable culturing T cells with high cell viability, low DNA damage, high growth rate (≈320‐fold expansion over 14 days), high purity (≈98% CD3+), and high yield (≈3.2 × 10 8 cells mL −1 hydrogel). All offer considerable advantages compared to current T cell culturing approaches. This new culture technology can significantly reduce the culture volume, time, and cost, while increasing the production. Abstract : A novel method is developed for culturing human T cells. Cells are cultured within microscale alginate hydrogel tubes suspended in cell culture medium. The tubes protect cells from hydrodynamic stresses, prevent excessive cell aggregation, and confine the cell mass less than the diffusion limit (in radial diameter), together creating friendly microenvironments for T cell growth.